(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article discusses the role of folklore and religion in imparting knowledge of natural sciences, in particular nature, to the younger generation, as well as the continuity of the educational process. In addition, the article discusses the content and essence of concepts about nature, what proverbs and riddles exist in folklore about nature, and what functions they perform in nature, as well as the diversity of existing species and what purposes they are used in nature, and argues that it is important to instill in the minds of young people from childhood that it is the duty of every person to preserve nature and consider it sacred. The article also discusses issues such as measures to protect nature and increasing knowledge about nature among young people.